2000
DOI: 10.1002/(sici)1097-4636(200001)49:1<134::aid-jbm17>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatments on tendon cellularity and mechanical properties

Abstract: Removal of cells may decrease the antigenicity and risk of disease transmission associated with tendon al-lografts and xenografts. An ideal cell removal method would not compromise graft structure and mechanical properties. This study compared the effects of three extraction chemicals [t-octyl-phenoxypolyethoxyethanol (Triton X-100), tri(n-butyl)phosphate (TnBP), and sodium dodecyl sulfate (SDS)] on tendon cellularity, structure, nativity, and mechanical properties. Rat tail tendons were soaked in extraction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(138 citation statements)
references
References 19 publications
5
132
0
1
Order By: Relevance
“…Some detergents can induce alterations in the collagen fibers resulting in decreased mechanical stability of the tissue 52,53 .…”
Section: Decellularization Effect On the Ecmmentioning
confidence: 99%
“…Some detergents can induce alterations in the collagen fibers resulting in decreased mechanical stability of the tissue 52,53 .…”
Section: Decellularization Effect On the Ecmmentioning
confidence: 99%
“…Many organs, e.g. urinary bladder [6], small intestinal [7][8][9][10][11], heart valves [12][13][14][15], skin [16,17], liver [18], anterior crucial ligament bone [19], kidney [20], pericardium [21], blood vessels [22], nerves [23], skeletal muscle [24], tendon [25] and vocal cord [26,27] from bovine and porcine tissues, have been used for fabricating the ECMbased scaffold. But, the use of goat-lung has not been focused for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…10 The ideal scaffold should not only be biocompatible and match the natural biomechanical properties, but should also comprise naturally structured, extracellular matrix proteins that can interact with the repopulating cells and direct them toward tenogenic differentiation and matrix remodeling. 10,11 Decellularization of tendon tissue offers the unique opportunity of obtaining a scaffold with a natural extracellular matrix structure that is hypoimmunogenic 13,14 and displays biomechanical properties very similar to the original tissue, [15][16][17][18] providing great advantages for potential clinical application and research use.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Results obtained after applying different detergent-based protocols remain conflicting. While t-octyl-phenoxypolyethoxyethanol (Triton X-100) did not lead to satisfactory results in an early study, 15 it was found to be most effective by others. 19 Sodium dodecyl sulfate (SDS) was reported to be effective but to reduce cytocompatibility due to matrix alterations; however, the protocol used in these studies did not only include incubation in SDS, but also in Triton X-100.…”
Section: Introductionmentioning
confidence: 99%